The role of interleukin-1 gene polymorphisms and Helicobacter pylori in gastroesophageal reflux disease - Akçil, Gülhan; Doğan, İbrahim and Cengiz, Mustafa and Engin, Evren Doruk and Doğan, Mehmet and Ünal, Selahattin and Yalınay Çırak, Meltem and Dursun, Ayşe (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Our aim is to assess the relationship between interleukin 1β (IL-1 β), (-511,-31 alleles), interleukin 1RN (IL-RN), Helicobacter pylori (HP) status and gastroesophageal reflux disease (GERD) diagnosed by pH monitoring in the Turkish population. Materials and Methods: A Total of 100 consecutive patients with GERD were enrolled in the study. Genotypes of IL-1β (-511,-31), IL-1RN gene polymorphisms and HP status of the patients were analyzed. Results: While thirty-two patients were diagnosed as esophagitis with varying severity the remaining patients had no esophagitis. Seventy six participants were positive for HP and the remaining patients were negative. The difference between erosive and non-erosive groups was statistically significant when we compared IL-1β (-511) but no difference regarding IL-1β (-31) and IL-1RN variations. We also analyzed T/T, C/T and C/C alleles and the difference was significant statistically in T/T allele between patients with and without erosive GERD 1 (3.1%) vs. 12 (17.9%), respectively with a p value <0.05. But C/C, C/T alleles of (-511), (-31) and IL-1RN polymorphisms were not statistically significant between the groups. Conclusion: IL-1β genetic polymorphisms may take part in the pathophysiology of gastroesophageal reflux disease.